Análisis y determinación de la cantidad de gases de efecto invernadero del Centro Binacional de Formación Técnica Zapotepamba de la Universidad Nacional de Loja - Torres Guamán, Santos Agustín (2016)
Climate change is an environmental problem with major global incidence in recent years. Its negative effects are watching all over the planet. This global warming is directly related to human, especially the production of electricity, industry, agriculture, livestock, deforestation and transport activity. International concern about the adverse consequences of climate change, has led to various organizations and institutions to take steps to fully understand the dynamics of greenhouse gases (GHGs). One of the internationally recognized indicators to understand the dynamics is the carbon footprint which is obtained by quantifying GHG emissions arising from the activities of an individual, organization, over a period of time, expressed in t CO2 equivalent. In this research, an analysis of greenhouse gas Binational Center for Technical Training Zapotepamba developed. The investigation thus emissions of carbon dioxide, carbon monoxide, methane was determined by identifying activities that emit gases such as enteric fermentation of cattle and goats of the birds, and the management of solid and liquid waste and livestock consumption diesel fuel as it brings with 268.8 kg CO2 per year and diesel and gasoline 894,715584 kg CO2 por año per year and energy consumption 2 kW year and use of paper is 96 250 t CO2 per year. The results of greater impact are fuels, this gives guidelines to reduce GHG emissions to peak by using the 3 R: reduce, recycle, reuse.